IMPLEMENTASI NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK - Permadi, Lambertus Doni; Widiatna, Alexius Dwi (Bahasa Indonesia, 2025)
The application of multicultural education values ​​in the Catholic Religious Education learning process aims to form a generation that upholds the value of unity, develops an attitude of tolerance, mutual respect and respect for every difference. The multicultural education is done considering that Indonesian society and nation are formed from various tribes, religions, cultures, social statuses, ethnicities and different bloodlines. Ignoring multicultural education in the learning curriculum at school can result in students not learning to respect each other and differences. Lack of appreciation and respect for differences in a multicultural society can give rise to misunderstandings, conflicts and divisions. The research method used is qualitative research. Data collection was done through observation, interviews and documentation. The focus of this research is the implementation of multicultural education values ​​through Catholic Religious Education subjects. The research results show that Catholic religious teachers have succeeded in designing strategies and effectively implementing the values ​​of multicultural education through Catholic Religious Education subjects in schools.